Extended Ginzburg-Landau theory and spatial scales of band condensates - SARAIVA, Tiago Teixeira (2018)
The Thesis is focused on superconducting phenomena that can not be captured by the standard Ginzburg-Landau (GL) theory. Furthermore, the phenomena of interest can hardly be investigated in necessary detail by means of the full microscopic formalism, due to abnormal technical difficulties. This is why the present study is performed within the extended GL formalism (SHANENKO et al., 2011; VAGOV et al., 2012) that goes to one order beyond the GL theory in the perturbation expansion of the microscopic equations over the proximity to Tᴄ but can still be analytically solved in many physically important cases. One of those phenomena is the formation of a finite intertype domain (AUER; ULLMAIER, 1973; BRANDT; DAS, 2011; VAGOV et al., 2016) in the phase diagram between standard superconductivity types I and II, where the superconducting magnetic response cannot be classified in the conventional terms. First evidences of such a domain date back to 1960’s but little was known about effects of the anisotropy on its formation. This point has been clarified in the present Thesis. It has been recently demonstrated (VAGOV et al., 2016) that the intertype domain is expanded in the presence of multiple bands (multi-band superconductors) with different spatial scales. Important competition between band length scales arises from nonlocal effects beyond the standard GL approach (SARAIVA et al., 2017). It has been demonstrated in the Thesis that a notable deviation between the coherent scales of different band condensates can appear even far beyond the regime of nearly decoupled bands. This allows for a deeper insight on how the band length scales depend on microscopic parameters and will certainly be appealing to experimentalists, as the conclusions are relevant for the spatial distribution of the superconducting condensate in the vortex core of multi-band materials and their possible intertype magnetic response.